2015
DOI: 10.1016/j.fct.2015.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol prevents protein nitration and release of endonucleases from mitochondria during acetaminophen hepatotoxicity

Abstract: Overdose of acetaminophen (APAP) is a common cause of acute liver injury and liver failure. The mechanism involves formation of a reactive metabolite, protein binding, oxidative stress and activation of c-Jun N-terminal kinase (JNK), mitochondrial dysfunction, and nuclear DNA fragmentation caused by endonucleases released from damaged mitochondria. Previous work has shown that the natural product resveratrol (RSV) can protect against APAP hepatotoxicity in mice through prevention of lipid peroxidation and anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 72 publications
(108 reference statements)
1
38
0
Order By: Relevance
“…Metabolism of APAP to its reactive metabolite by Cyp2e1, subsequent APAP-protein binding, and initiation of necrosis signaling are critical to induction of AILI [41]. Interference with these early events affect the severity of hepatotoxicity, especially when a compound or its vehicle is administered simultaneously with, or before APAP [41].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolism of APAP to its reactive metabolite by Cyp2e1, subsequent APAP-protein binding, and initiation of necrosis signaling are critical to induction of AILI [41]. Interference with these early events affect the severity of hepatotoxicity, especially when a compound or its vehicle is administered simultaneously with, or before APAP [41].…”
Section: Discussionmentioning
confidence: 99%
“…Berries, nuts, grapes RSV decreased protein nitration after APAP treatment, possibly through direct scavenging of peroxynitrite. RSV also inhibited release of apoptosis-inducing factor and endonuclease G from mitochondria independent of Bax pore formation and prevented the downstream nuclear DNA fragmentation Du et al (2015) Aloe vera Aloe vera The mean level of ALT, hepatic MDA, the number of IL-12 and IL-18 positive-stained cells, and hepatic GSH in Aloe vera-treated group were improved as compared with APAP group. Moreover, in the APAP group, the liver showed extensive hemorrhagic hepatic necrosis at all zones while in Aloe vera-treated group, the liver architecture was improved histopathology Werawatganon et al (2014) Apigenin Parsley, onions, oranges, tea, and chamomile…”
Section: Funding Informationmentioning
confidence: 95%
“…The mechanisms that may explain this protection include antioxidant effects, up-regulation of phase II enzymes, modulation of inflammatory responses and induction of mitochondrial biogenesis (Baur et al 2006;Sener et al 2006;Lagouge et al 2006;Masubuchi et al 2009;Bishayee et al 2010). Du et al (2015) administered male mice with APAP (300 mg/kg) and 1.5 h later with RSV (50 mg/kg). RSV reduced liver injury after APAP overdose in mice.…”
Section: Resveratrolmentioning
confidence: 99%
“…Though not yet confirmed in a stroke model, resveratrol scavenges ONOO - and inhibits protein nitration in several other models [139,140,141]. Moreover, liquid chromatography with tandem electrospray mass spectrometry showed that resveratrol is a substrate of ONOO - .…”
Section: Active Compounds From Chinese Herbal Medicine For Targeting mentioning
confidence: 99%